Huququl Insan Wajhatu Nadhara Islamiyyah - Asmuni Thahir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2001)
The Islamic ideas of human rights came long with the born of Islam its self. But the brilliant ideas about it were started to elaborate and to develope by Moslem intellectual in the end of forties together with the born of higher spirit to come back to Qur'anic concept regarding